Study of the Proportion of Catfish and Duck Meat on the Physicochemical Characteristics of Nugget with the Addition of Sodium Alginate Binding Material - Ferdianza, Ryan Setya; Winarti, Sri (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
A nugget is a type of processed meat restructuring, namely meat that is ground and seasoned, then enveloped by flour adhesive and breadcrumb coating (breading). The purpose of this study was to evaluate the effects of different proportions of catfish and duck meat, as well as the addition of sodium alginate, on the physicochemical and organoleptic characteristics of nuggets. This study used a factorial completely randomized design (CRD) with two factors and two replications. Factor I is the treatment of the proportion of catfish and duck meat. Factor II is the addition of sodium alginate binder (0.5%; 0.75%, or 1%). The data obtained were analyzed using analysis of variance (ANOVA) with a significance level of 5%. If there were differences between treatments, then DMRT 5% further test was conducted. The best results came from using a mix of 70% catfish and 30% duck meat with 1% sodium alginate, which created nuggets with 59.32% moisture, 1.28% ash, 8.75% fat, 16.86% protein, a texture value of 563.470 gf, and a water binding capacity of 81.74%. In the taste test, the average scores were 4.12 for color (slightly like), 4.01 for aroma (slightly like), 3.88 for taste (like), and 3.72 for texture (like). Contribution to Sustainable Development Goals (SDGs)SDG 2–Zero Hunger:SDG 3 – Good Health and Well-being:SDG 9 – Industry, Innovation, and Infrastructure:SDG 12 – Responsible Consumption and Production: